2004
DOI: 10.1080/00016480310016037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of nasal polyps in individuals recruited from a general population-based study

Abstract: Nasal polyps alone, as seen occasionally, are indicative of airway disease involving the upper and lower respiratory tracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 13 publications
0
32
1
1
Order By: Relevance
“…In the 2 previous studies, 17,19 baseline symptom scores indicated that subjects found nasal congestion/obstruction and loss of sense of smell to be more serious than other nasal symptoms, as has been previously reported. 16,20 From this data analysis, subjects experienced a statistically significant improvement in sense of smell on day 13, which persisted for the 4-month study period. 17,19 The lack of statistical significance for improvement of sense of smell on individual days may be secondary to the observed placebo effect.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the 2 previous studies, 17,19 baseline symptom scores indicated that subjects found nasal congestion/obstruction and loss of sense of smell to be more serious than other nasal symptoms, as has been previously reported. 16,20 From this data analysis, subjects experienced a statistically significant improvement in sense of smell on day 13, which persisted for the 4-month study period. 17,19 The lack of statistical significance for improvement of sense of smell on individual days may be secondary to the observed placebo effect.…”
Section: Discussionmentioning
confidence: 85%
“…6 Topical intranasal corticosteroids, which inhibit the eosinophil-associated inflammation found with polyposis without affecting the immune response, have been shown in numerous studies to reduce polyp grade (size and extent), improve symptoms, and delay or reduce the need for surgery. 2,[8][9][10][11][12][13][14][15][16][17] Intranasal corticosteroids are currently considered the medical treatment of choice for nasal polyposis. 18 In 2 recent, large, multicenter, placebo-controlled studies, mometasone furoate nasal spray (MFNS) demonstrated significant, lasting symptom relief compared with placebo in nasal congestion/obstruction, anterior rhinorrhea, and postnasal drip scores, and significantly improved sense of smell.…”
mentioning
confidence: 99%
“…Baseline symptom scores indicated that subjects found congestion/obstruction and loss of smell more serious than other nasal symptoms, as in other studies of nasal polyposis. 23,24 Both dosage regimens were significantly more effective than placebo in substantially reducing polyp size and extent over the course of the study, with no statistically significant differences observed between the 2 active treatment groups. At the end of the treatment period, the change in bilateral polyp grade score overall with MFNS treatment represented a clinically significant reduction of approximately 30% relative to baseline score.…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, the prevalence of asthma in patients with CRSwNP never referred for ESS remains largely unknown. 16,20 The asthma prevalence in Denmark is 7-10% in the general population, thus similar to that of other industrialized countries. 29,30 We recently studied patients in SC with CRSwNP referred for ESS and report a very high prevalence of asthma (65%) in this group.…”
mentioning
confidence: 83%